Pattern of pulmonary function tests in subjects recovered from COVID 19 infection - K S, Chaithanya; Basti, Anahita R Shenoy; Prabhu, Srilakshmi M (National Board of Examinations Journal of Medical Sciences, 2024)
Introduction and Aim: The pulmonary sequelae of COVID-19 have not been extensively studied in the Indian population. This study was taken up with the aim to assess the pulmonary function tests (PFT) in subjects recovered from COVID-19. Material and Methods: In this observational cross-sectional study PFT was assessed in 50 adults in the age group of 18-60years. Rapid Antigen Testing was performed to rule out active COVID-19 infection. Subjects with acute or chronic respiratory illnesses that could affect lung functions were excluded. Results: We performed PFT on 50 subjects, with a mean age and BMI of 36.09 years and 25.17 kg/m2. Fatigue and/or breathlessness were the most common complaints present post-recovery. A normal PFT was found in 22 participants and 28 showed a restrictive pattern. Based on the severity of the disease they had experienced the study population was classified into three groups mild, moderate or severe COVID. The three groups were found to be comparable in their demographic parameters, the PFT parameters were significantly different between the groups with significantly lower values seen in subjects who recovered from severe COVID. Conclusions: Restrictive pattern on PFT was the common abnormality found in patients recovered from COVID-19. This finding emphasises the need for long-term follow-up and establishment of a plan of assessment and management in patients recovered from COVID-19.